ANALISIS PENGARUH BEBAN KERJA, LINGKUNGAN KERJA DAN PENGALAMAN KERJA TERHADAP STRES KERJA PADA KARYAWAN PT. PELAYARAN SINDUTAMA BAHARI CABANG LEMBAR - Sudarta Sudarta (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2015)
An analysis of the influece of workloads, work environments and work experiences on jobstresses experienced by the employees of PT. Pelayaran Sindutama Bahari of Lembar BranchOffice.Barriers and constraints related to work, such as inappropriate workloads, work environmentsand work experiences can trigger job stresses as experienced by the employees PT. PelayaranSindutama Bahari of Lembar Barnch Office. This study aims to reveal whether the workloads,work environments and work experiences had a significant effect on the emplyees’ stresses eithersimultaneously or partially.This is an assoociative research study. Population and samples of this stydy were all employeesof PT. Sailing Sindutama Lembar Marine Branch (80 people). A questionnaire was used asinstrument to gather the data. This instrument contained questions about workloads, workenvironments and work experiences. Data were analyzed Multiple Linear Regression Analysis.Result of the study show that workloads, work environments and work exprience simultaneouslyand partially had a significant effect on teh depnedent variable of work stresses. The variableofwork environmetn was found to be the most dominant varable affecting job stresses. Based onthese results, the researcher suggests that teh management of PT Sailing Sindutama MarineBranch Lembar evaluate is previous policies, particularly th one which might potentially havecaused the emergence of stresses among employees. Furthermore, it is suggested that thepersonnel management place its staff based on theri level of competences so that all employeesfelt encouraged to create better performance.